2016
DOI: 10.14814/phy2.12790
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofε-viniferin, a dehydrodimer of resveratrol, on transepithelial active ion transport and ion permeability in the rat small and large intestinal mucosa

Abstract: ε‐Viniferin is a dehydrodimer of resveratrol, a polyphenol synthesized in many plants, including grapevine. The present study investigated the effects of ε‐viniferin and resveratrol on epithelial secretory and barrier functions in isolated rat small and large intestinal mucosa. Mucosa–submucosa tissue preparations of various segments of the rat large and small intestines were mounted on Ussing chambers, and short‐circuit current (I sc) and tissue conductance (G t) were continuously measured. The mucosal additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It was reported that ε-viniferin disappeared rapidly in DMEM medium, and ε-viniferin was rapidly glucuronidated after incubations with liver microsomes . It was also reported that the administration of ε-viniferin to the mucosal side of the rat intestine regulated transepithelial ion transport, ion permeability, and nonionic macromolecule permeability, which revealed ε-viniferin had beneficial effects on intestinal functions by enhancing the mucosal host defense mechanism . ε-Viniferin is the resveratrol dimer, and it was proposed that the anti-adipogenic and/or anti-obesity mechanisms of (+)-ε-viniferin might be similar to those of resveratrol and need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ε-viniferin disappeared rapidly in DMEM medium, and ε-viniferin was rapidly glucuronidated after incubations with liver microsomes . It was also reported that the administration of ε-viniferin to the mucosal side of the rat intestine regulated transepithelial ion transport, ion permeability, and nonionic macromolecule permeability, which revealed ε-viniferin had beneficial effects on intestinal functions by enhancing the mucosal host defense mechanism . ε-Viniferin is the resveratrol dimer, and it was proposed that the anti-adipogenic and/or anti-obesity mechanisms of (+)-ε-viniferin might be similar to those of resveratrol and need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…42 It was also reported that the administration of εviniferin to the mucosal side of the rat intestine regulated transepithelial ion transport, ion permeability, and nonionic macromolecule permeability, which revealed ε-viniferin had beneficial effects on intestinal functions by enhancing the mucosal host defense mechanism. 43 ε-Viniferin is the resveratrol dimer, and it was proposed that the anti-adipogenic and/or anti-obesity mechanisms of (+)-ε-viniferin might be similar to those of resveratrol and need to be investigated further. Chen et al 44 reported that resveratrol exhibited a dosedependent (20, 40, and 80 μM) anti-adipogenic effect in differentiated 3T3-L1 adipocytes by reducing gene and protein expression levels of PPARγ, etc.…”
Section: ■ Discussionmentioning
confidence: 99%
“…FITC was known to be a large fluorescent substance and fluorescence value could reflect permeability of mucosal epithelium. 22 The logarithmic growth cells of each group were inoculated into the upper chamber of the 24-well Transwell plate (1×10 5 cells per well). A 100 μL and 600 μL of culture medium were added to the upper and lower chamber, respectively, in a 5% CO 2 incubator at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Ussing chamber experiments. Ussing chamber experiments were performed following a method described previously (19). Mucosa-submucosa preparations were mounted on the Ussing chambers (cross-sectional area: 0.64 cm 2 ; CHM2, World Precision Instruments (WPI), Inc., Sarasota, FL, USA) with a pair of aluminum foil ribbon electrodes for electrical field stimulation (EFS).…”
Section: Methodsmentioning
confidence: 99%